Gamma Radioactivity of the January 2013 Rainfall in Ostrava - Alexa, Petr; Količová, Petra; Uhlář, Radim (GeoScience Engineering, 2014)
Gamma radioactivity of an 8 mm thick ice layer formed after a modest rain on 21 January 2013 in the VŠB-Technical University of Ostrava campus was analyzed and gamma-ray emissions from primordial 40K have been found. Cosmogenic 7Be produced mainly in galactic cosmic-ray spallation processes on atmospheric nitrogen and oxygen and 226Ra, 235U and 137Cs have been also observed.